Cover Feature: Smart Control of Composition for Double Perovskite Electrocatalysts toward Enhanced Oxygen Evolution Reaction (ChemSusChem 23/2019). Issue 23 (26th November 2019) - Sun, Hainan; Xu, Xiaomin; Chen, Gao; Zhou, Yupeng; Lin, Hong‐Ji; Chen, Chien‐Te; Ran, Ran; Zhou, Wei; Shao, Zongping
Abstract : The Cover Feature shows how oxygen evolution reaction (OER)‐active elements are simultaneously introduced into the B‐site and B′‐site of a B‐site‐ordered double perovskite (A2 BB′O6 ), leading to an enhancement in the exposed reactive sites and an optimum surface chemical state. The A2 BB′O6 perovskite displays remarkably long durability and excellent OER activity. More information can be found in the Full Paper by H. Sun et al. on page 5111 in Issue 23, 2019 (DOI: 10.1002/cssc.201902138 ).